Implementasi Supervisi Klinis dalam Meningkatkan Kemampuan Mengajar Guru Mata Pelajaran Akidah Akhlak - Slamet Riyadi (Faculty of Education Universitas Negeri Malang, 2016)
Abstract: Implementation of Clinical Supervision in improving the Ability of Teachers to Teach the Subjects Moral Creed. Clinical supervision is one of the efforts in improving the professionalism of teachers. This research aims to (1) find out the implementation of clinical supervision in improving the ability of teaching; and (2) determine whether clinical supervision techniques can increase the ability of teachers to teach the subjects Moral Creed on MAN Rejotangan Tulungagung. This research uses the qualitative descriptive method with the class action research design. The results showed that the implementation of clinical supervision is going well and can increase the capability of the teachers teaching in the subjects Moral Creed.Abstrak: Implementasi Supervisi Klinis dalam Meningkatkan Kemampuan Mengajar Guru Mata Pelajaran Akidah Akhlak. Supervisi klinis merupakan salah satu upaya dalam meningkatkan profesionalisme guru. Penelitian ini bertujuan untuk (1) mengetahui implementasi supervisi klinis dalam meningkatkan kemampuan mengajar; dan (2) mengetahui apakah teknik supervisi klinis dapat meningkatkan kemampuan mengajar guru mata pelajaran Akidah Akhlak di MAN Rejotangan Tulungagung. Penelitian ini menggunakan metode deskriptif kualitatif dengan rancangan penelitian tindakan kelas. Hasil penelitian menunjukkan bahwa pelaksanaan supervisi klinis berjalan dengan baik dan dapat meningkatkan kemampuan mengajar guru pada mata pelajaran Akidah Akhlak.